2012
DOI: 10.1167/iovs.12-10385
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor H Deficiency Results in Decreased Neuroretinal Expression ofCd59ain Aged Mice

Abstract: While the connection between CFH deficiency and failure to upregulate CD59a remains unknown, these results suggest that expression of CD59 is tissue-specific and that neuroretinal regulation depends on CFH. This could contribute to the visual functional deficits and morphological changes in the Cfh(-/-) mouse retina that occur with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…The requirement for protection against complement activation clearly exists in the retina since rod and cone photoreceptors in human eyes, and astroglial cells in mouse eyes have been shown to express DAF [6, 7], and we also reported that CD59a and CFH are up-regulated in the mouse neuroretina in normal ageing, again supporting the idea that complement regulation is required for maintenance of a healthy retina [8]. …”
Section: Introductionsupporting
confidence: 75%
“…The requirement for protection against complement activation clearly exists in the retina since rod and cone photoreceptors in human eyes, and astroglial cells in mouse eyes have been shown to express DAF [6, 7], and we also reported that CD59a and CFH are up-regulated in the mouse neuroretina in normal ageing, again supporting the idea that complement regulation is required for maintenance of a healthy retina [8]. …”
Section: Introductionsupporting
confidence: 75%
“…We also showed that FADS1 expression is significantly increased in RPE-choroid, but not neuroretina, of young Cfh null mice, an early-stage AMD model [21]. FADS1 and FADS2 encode delta-5 and delta-6 desaturases, respectively, which are membrane-bound enzymes that catalyze the formation of long-chain polyunsaturated fatty acids such as DHA and eicosapentaenoic acid (EPA) [43].…”
Section: Discussionmentioning
confidence: 94%
“…In two-year old Cfh −/− mice, we observed a number of abnormalities including reduced visual acuity and loss of rod function, and structural changes to the photoreceptors and Bruch’s membrane but it is not known when these functional and anatomical abnormalities begin in Cfh −/− mice. In a separate study we performed a microarray analysis of neural retina and retinal pigment epithelium (RPE) from these mice to investigate the consequences of Cfh deletion on age-related changes in gene expression, and observed anomalies in the expression patterns of certain complement regulators as a function of age [12].…”
Section: Introductionmentioning
confidence: 99%